Callus Induction and Differentiation on Melon From In Vitro Culture with The Addition of Indole Acetic Acid and Benzyl Amino Purine Growth Regulator - Probowati, Wiwit; Daryono, Budi Setiadi (Universitas Muhammadiyah Yogyakarta, 2018)
Melon plants (Cucumis melo L.) are susceptible to disease attacks primarily caused by viruses. One of the viruses often attacking melon plants is Cucumber mosaic virus (CMV). Previous studies have shown that melon callus produced from in vitro culture is detected to have CMV resistance gene (Creb-2). However, the trait of resistance to CMV in that melon (F2) is still segregated. To know the stability of the Creb-2 gene, further research is needed to detect the gene in the differentiated callus. This study aims toÂ callus induce and callus differentiate melon. Firstly, melon seeds were grown on Â¼ MS medium with addition of 2 mg / L 2.4-Dichlorophenoxyacetate and 1 mg / L BAP (Benzyl Amino Purine) to grow callus. Secondly, the callus was differentiated in MS medium with the addition of 2,4-D , BAP and IAA in different doses. 0 mg / L; 0.01 mg / L 2.4-D and 0.1 mg / L BAP, and MS medium with 0.01 mg / L; 0.1 mg / L; 1 mg / L IAA (Iodole Acetic Acid) and 0.1 mg / L BAP. The results showed that callus was successfully differentiated into root and it grew optimally in MS medium with 0.01 mg / L 2.4-D: 0.1 mg / L BAP and 1 mg / L IAA: 0.1 mg / L BAP . Therefore the roots can be used as isolation samples and DNA amplification to detect stability of the Creb-2 gene.